Development of df/dt function in inverters for synthetic inertia - Jun Hashimoto; Taha Selim Ustun; Dai Orihara; Hiroshi Kikusato; Kenji Otani; Kazuo Suekane; Takehiro Miyake; Hiroyuki Namari; Hajime Yamamoto; Takahiro Matsuura; Satoshi Miyazaki; Hiromu Hamada; et al. (Energy Reports, 2023)
The increasing share of renewable energy-based resources in the power grid has a detrimental impact on the power system stability. As these resources are inverter-based, they decrease the overall inertia of the grid. To mitigate this problem, recent research focuses on developing novel techniques to provide synthetic inertia with inverters. In this fashion, inverter-based resources (IBR) can also contribute to power system inertia, hence, its stability. Some of the approaches for providing synthetic inertia are discussed in the standards. However, despite its potential, frequency-derivate-based (df/dt) solutions are not studied to adapt grid code in Japan. This paper addresses this need by developing a full df/dt control approach for IBRs. Several intricacies of this design is presented along with operation curves and system designs. Considering the special needs of the Japanese Electrical Grid, and the speed in which inertia support should be provided, a novel rate of change of frequency (RoCoF) measurement approach is also developed and presented. Lab tests are performed with hardware-in-the-loop tests and the results validate the operation and performance of both novel RoCoF measurement and df/dt control model.